Effects of europium doping on thermal property and failure behaviour of Gd2Zr2O7 thermal barrier coatings - Zaoyu Shen; Yuqing Luo; Guanxi Liu; Jianwei Dai; Limin He; Rende Mu (npj Materials Degradation)
Abstract This work concentrates on the phase, composition, thermo-physical properties, microstructure, service lifetime, and failure behaviour of GdEuZrO/YSZ thermal barrier coatings fabricated via electron beam-physical vapor deposition. The thermo-physical property of the GdEuZrO ceramics are superior to Gd2Zr2O7 and YSZ due to the substitution of Eu. A feathery structure characterized by inner-gaps and linear pores is observable at the column tips. The GdEuZrO/YSZ TBCs have demonstrated the most extended service lifetime compared to YSZ or GdEuZrO TBCs. The high thermal expansion coefficient, the feathery microstructure, the low thermal conductivity, and the substitution effect of Eu are key contributors to the enhanced thermal durability of the TBCs. After the thermal cycling test, the outward migration of Ni, Cr, Co, Al, and Hf elements results in the emergence of Ni-Cr-Co-Al-Hf oxides. The migration of elements and the progression of cracks are identified as the primary causes of failure in the GdEuZrO/YSZ TBCs.